The feeding habits of Wiseana (Lepidoptera: Hepialidae) species on a traditional Māori food crop. Issue 1 (2nd January 2020) - Ehau-Taumaunu, H.; Marshall, S. D. G.; Ferguson, C. M.; Mark-Shadbolt, M.; MacDiarmid, R. M.; O'Callaghan, M.
ABSTRACT: For Māori the kūmara symbolises the extensive voyages from the ancestral home of Hawaiki to Aotearoa New Zealand and the ingenuity needed to adapt growing practices for a tropical crop to the climate of New Zealand. From the thirteenth century, kūmara cultivation occurred along the coastlines in the warmer regions of New Zealand where its associated pests were controlled by traditional methods. In 1952, an observation was made indicating that Wiseana, an endemic genera of ghost moths, possibly fed on kūmara. The current study investigates the feeding habits and preferences of laboratory-reared Wiseana copularis and W. cervinata larvae for kūmara through no-choice and choice test bioassays. Kūmara tuber provided the largest mean weight gain for the two Wiseana species with a 122% increase by week 6 compared to white clover foliage. The mean weight gain of larvae fed with kūmara leaf, kūmara stem or white clover were not significantly different. All kūmara and white clover options were equally selected by larvae within the two-choice tests, therefore there was no differential preference for the kūmara plant material. This data indicates that the polyphagous herbivore larvae of Wiseana spp. may have fed on kūmara in traditional kūmara gardens, supporting the early published record. Further research is needed to determine if Wiseana larvae are affecting kūmara production today. Ki te Māori ko te kūmara e hua ai ngā hekenga maha ā ngā tīpuna mai i a Hawaiki ki Aotearoa, me ā rātou mōhiotanga ki te whakatipu i te kūmara ki te āhuarangi mātoke o Aotearoa. Nō te rautau tekau mā toru i whakatipu ai ngā kumara ki ngā takutai o Aotearoa ā, i āraia atu ngā mate, ngā kīrearea mā te whakaritenga tūturu. I te tau 1952 nō te tirohanga mai o te porina (Wiseana) kainga pea e te pūrehurehu taketake i ngā kūmara. Ko te rangahau o naianei ko ngā whiringa me ngā hiahia o te kai ā ngā torongū porina i whakatipu ai i roto i te taiwhanga pūtaiao ki roto i te whakamātau kore-kōwhiri, te whakamātau kōwhiri rānei. Ko te kōpura i whakaputa ai i te taumaha nui ake i te 122% i te taumaha o te korowa i te wiki tuaono. Kāhore he taumaha tino rerekē mō te whā me te kakau o te tipu ki te korowa. Kei roto i te kōwhiri whakamatau, ko ngā kūmara katoa me ngā korowa i kōwhiringia ōritengia ai e te huhu, nā reira kaore kau he mea rerekē mo te hiahiatanga o te tipu kūmara. I te mutunga, ē whakaatu ana te raraunga nei, kainga pea e te kaitipu huhu i ngā kūmara o ngā māra tūturu, hei tautoko hoki tēnei i ngā tuhinga o mua. Ma te rangahau anō ka kitengia mehemea ka pāngatia tonutia e te huhu (Wiseana) i te whakanaonga o ngā kūmara o naianei.